Efficacy of panobinostat and marizomib in acute myeloid leukemia and bortezomib-resistant models. Issue 3 (March 2015) - Corrales-Medina, Fernando F.; Manton, Christa A.; Orlowski, Robert Z.; Chandra, Joya
Highlights Panobinostat elicits cell death in acute myeloid leukemia (AML) cell lines. Cell lines resistant to proteasome inhibitors are sensitive to panobinostat. Synergy is observed with panobinostat and proteasome inhibitors in AML lines.